Focal Increased Tc-99m MDP Uptake in the Nutrient Foramen of the Femoral Diaphysis on Bone SPECT/CT - Cha, Hwajin (Nucl Med Mol Imaging, 2017)
We present images of an 83-year-old female with a history of osteoporosis and bilateral total knee replacement arthroplasty, referred for bone scintigraphy and single-photon emission computed tomography (SPECT)/computed tomography (CT), owing to left knee pain. No trauma to, or intense exercise of, the knee was reported. The bone scan and SPECT/CT revealed a focally increased Tc-99m methylene diphosphonate (MDP) uptake in the medial cortex of the left femoral diaphysis with matched linear radiolucency on CT images. This was misinterpreted as atypical femoral stress fracture; however, focal stress reaction injury to the nutrient foramen was confirmed on contrast-enhanced magnetic resonance imaging.